2015
DOI: 10.1016/j.marchem.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth element cycling in a sandy subterranean estuary in Florida, USA

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
56
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 74 publications
13
56
0
Order By: Relevance
“…Rare earth element concentrations for coastal seawater and coastal groundwaters from the Kona Coast are presented in Table 4. Rare earth element concentrations of these coastal groundwaters are, on average, lower than in groundwaters from the Indian River Lagoon subterranean estuary in Florida (Johannesson et al, 2011;Chevis et al, 2015b).…”
Section: Ree Concentrations and Input-normalized Fractionation Patternsmentioning
confidence: 73%
See 1 more Smart Citation
“…Rare earth element concentrations for coastal seawater and coastal groundwaters from the Kona Coast are presented in Table 4. Rare earth element concentrations of these coastal groundwaters are, on average, lower than in groundwaters from the Indian River Lagoon subterranean estuary in Florida (Johannesson et al, 2011;Chevis et al, 2015b).…”
Section: Ree Concentrations and Input-normalized Fractionation Patternsmentioning
confidence: 73%
“…Nd concentration of 178 ± 12.9 pmol kg -1 (Table 4), whereas Nd concentrations measured in SGD from the Indian River Lagoon in Florida that were collected identically (i.e., 0.45 μm pore-size filters) range from 110 pmol kg -1 to 2409 pmol kg -1 , and exhibit a mean (±SD) Nd concentration of 448 ± 365 pmol kg -1 (n = 55; Johannesson et al, 2011;Chevis et al, 2015b). If the sample with the highest Nd concentration from the Indian River Lagoon subterranean estuary (i.e., 2409 pmol kg -1 ) is not included, the mean (±SD)…”
Section: Ree Concentrations and Input-normalized Fractionation Patternsmentioning
confidence: 99%
“…In general, high enrichment of REE, relative to the simple binary mixing of meteoric groundwater and seawater has been observed in STEs, although the STE can also act as a sink for heavy REEs (HREE) owing to adsorption onto Fe oxides (Johannesson et al, 2011). In STEs, light REEs (LREE) are more readily exchangeable on aquifer mineral surfaces than HREEs, and HREEs and middle REEs (MREE) exhibit a greater association with oxide minerals (Willis and Johannesson, 2011;Chevis et al, 2015). Thus, redox conditions along the flow path of groundwater can affect REE concentration and fractionation (Johannesson et al, 2005(Johannesson et al, , 2011Johannesson, 2005, 2006).…”
Section: Geochemical Processesmentioning
confidence: 99%
“…Thus, redox conditions along the flow path of groundwater can affect REE concentration and fractionation (Johannesson et al, 2005(Johannesson et al, , 2011Johannesson, 2005, 2006). A case study carried out on a sandy STE in Florida (Chevis et al, 2015) showed that advection and bio-irrigation differentially affect REE fluxes to the ocean as fresh groundwater is enriched in HREEs, while marine pore-water is enriched in MREE in association with the reductive dissolution of Fe oxides/oxyhydroxides. Therefore, REE contributions to coastal waters are clearly identified due to large contributions of different REE patterns to coastal waters (Kim and Kim, 2011;Johannesson et al, 2017).…”
Section: Geochemical Processesmentioning
confidence: 99%
See 1 more Smart Citation